High-strength extremely thick steel plate and method for manufacturing same

By controlling the steel structure and texture in high-strength thick-walled steel plates and optimizing the manufacturing process, the problem of poor brittle crack propagation stop characteristics in the prior art is solved, and the excellent toughness and brittle crack propagation stop characteristics of steel plates with yield strength of 500MPa are achieved, which is suitable for the application of high-strength structures.

CN119630826APending Publication Date: 2025-03-14JFE STEEL CORP

Patent Information

Application Number
CN202380059532.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-29
Filing Date
2023-11-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to achieve excellent brittle crack propagation stop characteristics in high-strength thick-walled steel plates, especially in steel plates with a yield strength of 500 MPa, and the manufacturing method is unstable and the efficiency is insufficient.

Method used

By controlling the composition and manufacturing process of the steel plate, it is ensured that the steel structure at 1/2 of the plate thickness is mixed with bainite and ferrite, the grains are finely refined, and the texture and cooling conditions are optimized during the rolling process to achieve excellent toughness and brittle crack propagation stop characteristics.

Benefits of technology

It realizes excellent brittle crack propagation stop characteristics and toughness in high-strength extremely thick steel plates, ensuring the safety and application performance of the steel plates, and is especially suitable for high-strength structures such as large container ships.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-strength extremely thick steel plate and a manufacturing method thereof. This high-strength extremely thick steel plate has a specific component composition, has a texture in which the X-ray intensity ratio of the (211) plane of the rolled surface at a position 1 / 2 of the plate thickness is 1.70 or more, and has a steel structure at a position 1 / 2 of the plate thickness, the steel structure at the position of 1 / 2 of the sheet thickness is a mixed structure comprising a bainite phase having an area fraction of 85-100% and a ferrite phase having an area fraction of 0-15%, the average crystal grain size of the bainite is 20 [mu] m or less, the equivalent circle diameter of the maximum pore remaining in the center of the sheet thickness is 200 [mu] m or less, the steel structure at the position of 1 / 2 of the sheet thickness is provided, the sheet thickness is 50-100 mm, and the thickness of the steel structure at the position of 1 / 2 of the sheet thickness is 50-100 mm. The yield strength at a position 1 / 2 of the sheet thickness is 500 MPa or more, the vTrs at a position 1 / 2 of the sheet thickness is-105 DEG C or less, and the value of Kca (-10 DEG C) is 9000 N / mm3 / 2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength, ultra-thick steel plate having excellent brittle crack propagation arrest characteristics and a method for producing the same which is suitable for use in large structures such as ships, marine structures, cryogenic storage tanks, building structures, and civil engineering structures. Background Art

[0002] Large structures such as ships, marine structures, cryogenic storage tanks, building structures, and civil engineering structures have a great impact on the social economy and the environment when accidents accompanied by brittle fracture occur. Therefore, large structures are always required to improve safety. For steel materials used in large structures, high levels of toughness and strength at operating temperature and brittle crack propagation stopping properties (crack arrest performance) are required to prevent brittle crack propagation.

[0003] Container ships and bulk carriers are not equipped with a general deck, but the cargo is loaded on the hatch cover. They travel on the ocean while bearing the waves that apply a large load. Therefore, they are repeatedly subjected to large bending stresses due to structural and operational reasons. Therefore, high-strength and thick-walled steel plates that can withstand the bending stress are usually used for the hull outer plate. In recent years, with the enlargement of the hull, the high-strength and thick-walled steel plates used have further developed.

[0004] Generally, the higher the strength or the thicker the wall thickness of a steel plate, the worse the brittle crack propagation arrest property. Therefore, when the steel plates used in container ships and the like in recent years have high strength and thick wall thickness, it is difficult to satisfy the required brittle crack propagation arrest property.

[0005] As a method for improving the brittle crack propagation arrest characteristics of steel materials, it is known in the past to increase the Ni content in steel. For example, in liquefied natural gas (LNG) storage tanks that require brittle crack propagation arrest characteristics at extremely low temperatures, 9% Ni steel is used on a commercial scale. However, the increase in the amount of Ni in the steel has to significantly increase the manufacturing cost, so it is difficult to apply it to uses other than LNG storage tanks.

[0006] On the other hand, for relatively thin steel materials with a thickness of less than 50 mm, such as those used in ships and pipelines, which cannot withstand extremely low temperatures like LNG, the TMCP (Thermo-Mechanical Control Process) method is used to achieve fine graining and improve toughness. This can provide excellent brittle crack propagation arrest properties.

[0007] For example, in Patent Document 1, the microstructure is a mixed structure of ferrite and bainite or a mixed structure of ferrite, pearlite and bainite, and the toughness is improved by controlling the average grain size at the center of the plate thickness to 5 to 20 μm. Thus, Patent Document 1 discloses a technology for improving the brittle crack propagation arrest property.

[0008] In order to improve the brittle crack propagation arrest property without increasing the alloy cost, Patent Documents 2 and 3, for example, disclose technologies for making the structure of the surface layer of a steel material ultrafine.

[0009] Patent Document 2 focuses on the effect of the shear lip (i.e., plastic deformation area) generated in the surface of the steel material when the brittle crack propagates, which is effective in improving the brittle crack propagation stopping characteristics. Patent Document 2 discloses that by making the grains of the shear lip part finer, the propagation energy of the propagating brittle crack is absorbed by the grains. In addition, in the manufacturing method of Patent Document 2, the surface part is cooled to a temperature below the Ar3 transformation point by controlled cooling after hot rolling, and then the controlled cooling is stopped, and the surface part is heated back to a temperature above the Ar3 transformation point. This process is repeated one or more times, and the steel material is pressed down. Therefore, Patent Document 2 discloses that by repeatedly causing phase transformation or processing recrystallization, an ultrafine ferrite structure or bainite structure is generated in the surface part.

[0010] In Patent Document 3, in order to improve the brittle crack propagation arrest characteristics in a steel material having a microstructure mainly composed of ferrite-pearlite, both surface portions of the steel material are made of a layer of a ferrite structure having ferrite grains having an equivalent circle grain size of 5 μm or less and an aspect ratio of 2 or more, accounting for 50% or more of the area, and at the same time, the fluctuation of the ferrite grain size is suppressed. As a method for suppressing the fluctuation, Patent Document 3 discloses suppressing the local recrystallization phenomenon by setting the maximum reduction rate per pass in the finishing rolling to 12% or less.

[0011] In addition, a method of improving the brittle crack propagation arrest property by applying reduction to the transformed ferrite to develop the texture during controlled rolling is also known. For example, the techniques of Patent Documents 4 and 5 can be cited.

[0012] In Patent Document 4, the texture is controlled as follows: the average equivalent circle diameter of the effective grains is 25 μm or less in the surface part of the thick steel plate, and is 35 μm or less in the center part of the plate thickness, and the texture strength ratio relative to the rolling surface and the rolling direction satisfies I{001}<110>+I{112}<110>+I{332}<113>>5, I{110}<001>+I{110}<110>+I{001}<010>≤3 in the surface part of the thick steel plate, and satisfies I{001}<110>+I{112}<110>+I{332}<113>≥3.5 in the center part of the plate thickness. Thus, Patent Document 4 discloses a technology for improving the brittle crack propagation arrest characteristics.

[0013] Patent Document 5 controls the steel plate in the following manner: the steel plate is divided into three layers: a surface and back layer portion from the front and back sides of the steel plate to 25% in the plate thickness direction, and a center portion of the plate thickness other than the surface and back layers. In the surface and back layers, a texture having a (100) X-ray surface intensity ratio of 1.5 or more and less than 2.0 parallel to the rolling surface is present in a region of 5% or more and 25% or less of the plate thickness, and a texture having a (111) or / and (211) X-ray surface intensity ratio of 2.0 or more parallel to the rolling surface is present in the center portion of the plate thickness. Thus, Patent Document 5 discloses a technique for improving the brittle crack propagation arrest characteristics.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: International Publication No. 2011 / 96456

[0017] Patent Document 2: Japanese Patent Application Publication No. 2002-256375

[0018] Patent Document 3: Japanese Patent Application Publication No. 2011-184754

[0019] Patent Document 4: Japanese Patent Application Publication No. 2012-172258

[0020] Patent Document 5: Japanese Patent Application Publication No. 2008-169467 Summary of the invention

[0021] Problems to be solved by the invention

[0022] However, in the techniques described in Patent Documents 2 and 3, only the surface layer of the steel is temporarily cooled and then reheated, and then processed during the reheating to obtain a specific structure. Therefore, it is difficult to control in actual production scale, and there is a problem of heavy load on rolling equipment and cooling equipment.

[0023] In addition, in the technologies described in Patent Documents 1 to 5, if the manufacturing conditions and the disclosed experimental data are all taken into consideration, the yield strength is mainly below 460 MPa. On the other hand, for large container ships of more than 24,000 TEU class required with the increase in logistics volume in recent years, it is necessary to use steel materials with a yield strength of 500 MPa class in the hatch side coaming from the viewpoint of ensuring the hull strength. However, it is unclear whether the specified characteristics can be obtained in the manufacturing methods of the above-mentioned patent documents.

[0024] Furthermore, as the strength of steel sheets increases, the required brittle crack propagation arrest characteristics increase. Therefore, for steel sheets with a yield strength of 500 MPa, a Kca value at -10°C (hereinafter sometimes referred to as "Kca (-10°C)") as a crack arrestability index is required to be 9000 N / mm. 3 / 2 However, such high-strength crack-arrest steel and a stable and efficient method for manufacturing the same have not yet been established.

[0025] Furthermore, in order to improve the brittle crack propagation arrest characteristics while maintaining the rigidity of the hull, even thick-walled materials of 50 mm or more and 100 mm or less are required to have both high strength and excellent toughness.

[0026] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a high-strength ultra-thick steel plate having excellent toughness and brittle crack propagation arrest characteristics even when the yield strength is 500 MPa class, and a method for producing the same.

[0027] Here, the term "high strength" in the present invention means that the yield strength (YS) of the high-strength ultra-thick steel plate at a position of 1 / 2 of the plate thickness is 500 MPa or more.

[0028] The term "excellent toughness" in the present invention means that the Charpy fracture transition temperature at a position of 1 / 2 of the plate thickness of the high-strength ultra-thick steel plate is vTrs≤-105°C.

[0029] In the present invention, "excellent brittle crack propagation stopping property (crack arresting property)" means that the value of Kca (-10°C) is 9000N / mm 3 / 2 above.

[0030] The steel plate having a yield strength of 500 MPa class is a steel plate having a yield strength of 500 MPa or more.

[0031] In addition, the yield strength, vTrs and Kca value can be measured by the method described in the Examples mentioned later.

[0032] Methods used to solve problems

[0033] In order to solve the above problems, the present inventors have repeatedly conducted intensive studies on a high-strength, ultra-thick steel plate having excellent brittle crack propagation arrest characteristics and toughness even when the yield strength is 500 MPa or more and good internal quality, and a method for stably obtaining the steel plate. As a result, the following findings were obtained.

[0034] It should be noted that the above-mentioned "good internal quality" refers to a state where the equivalent circle diameter of the largest pore remaining in the center of the steel plate is less than 200 μm. In order to achieve better internal quality, based on this condition, it is effective to form a state where the length of the largest pore remaining in the center of the steel plate in the thickness direction is less than 100 μm.

[0035] Specifically, in order to achieve a high strength of 500 MPa or more in yield strength, it is effective to control the carbon equivalent (Ceq) to 0.480 mass % or more.

[0036] In addition, in order to achieve the excellent toughness of the above-mentioned ultra-thick steel plate, it is effective to control the steel structure at the 1 / 2 position of the plate thickness so that the average grain size of the bainite grains surrounded by the grain boundaries with an orientation difference of 15° or more is less than 20μm and the equivalent circle diameter of the largest pore remaining in the center of the steel plate (1 / 2 position of the steel plate) is controlled to be less than 200μm. The toughness is improved by the effect of grain refinement, and the pores are not easy to become the starting point of fracture, so the Charpy toughness at the 1 / 2 position of the plate thickness with the lowest characteristics reaches vTrs≤-105℃.

[0037] As described above, in addition to setting the steel structure at 1 / 2 of the plate thickness to the above-mentioned structure, the toughness can be further improved by controlling the length of the largest pore remaining in the center of the steel plate in the plate thickness direction to be 100 μm or less.

[0038] In order to achieve the excellent brittle crack propagation arrest characteristics of the above-mentioned ultra-thick steel plate, it is effective to have excellent toughness and form a texture with an X-ray intensity ratio of (211) plane in the rolled surface at the half-thickness position of 1.70 or more. In this way, the linear progress of brittle cracks is suppressed, and the value of Kca (-10°C) (N / mm 3 / 2 ) reaches 9000N / mm 3 / 2 above.

[0039] Furthermore, in order to obtain the above toughness, in the hot rolling process, it is effective to control the cumulative reduction rate when the temperature at the 1 / 2 position of the plate thickness is within the austenite non-recrystallization temperature range to 50.0% or more, and to control the reduction ratio, which represents the ratio of the thickness of the steel billet to the plate thickness of the final product, to 4.00 or more. As a result, even an extremely thick steel plate with a plate thickness of 50 mm or more and 100 mm or less will not be affected by the plate thickness, and sufficient compressive stress can be applied to the 1 / 2 position of the plate thickness. As a result, the average grain size of the bainite grains can be controlled to the above-mentioned average grain size, and the pores at the 1 / 2 position of the plate thickness of the steel plate, which is the starting point of fracture, can be press-bonded, thereby achieving excellent toughness.

[0040] It should be noted that, regarding the above-mentioned “length of the largest pore in the plate thickness direction”, it is effective to appropriately control the average reduction ratio / pass number when the temperature at the position of 1 / 2 of the plate thickness is within the austenite recrystallization temperature range.

[0041] In addition, in order to obtain the above-mentioned brittle crack propagation stop characteristics, in the hot rolling process, the cumulative reduction rate within the above-mentioned austenite non-recrystallization temperature range is controlled to be above 50.0%, and the above-mentioned reduction ratio is controlled to be above 4.00, and the rolling end temperature at the 1 / 2 position of the plate thickness is controlled to be above the Ar3 point. Through this control, the grains of the steel structure at the 1 / 2 position of the plate thickness are made fine, and it is effective to control the texture at the 1 / 2 position of the plate thickness. As a result, while achieving excellent toughness, the austenite can be extended along the rolling direction, and the bainite phase transformation texture can be uniformly developed along a specific orientation. As a result, a texture with an X-ray intensity ratio of the (211) plane in the rolling surface at the 1 / 2 position of the plate thickness of 1.70 or more can be obtained.

[0042] The present invention has been completed by further studying the above findings, and the gist of the present invention is as follows.

[0043] [1] A high-strength, extra-thick steel plate having a composition comprising, in mass %, 0.040 to 0.130% C, 0.020 to 0.50% Si, 1.00 to 2.50% Mn, 0.020% or less P, 0.010% or less S, 0.010% or less Al, 0.0010 to 0.0100% N, and 0.0100% or less O, wherein Ceq defined by formula (1) is 0.480% or more, and the balance is Fe and unavoidable impurities,

[0044] The texture has an X-ray intensity ratio of the (211) plane in the rolled surface at a position of 1 / 2 of the plate thickness of 1.70 or more,

[0045] The steel sheet has a steel structure at a position of 1 / 2 of the plate thickness as described below, wherein the steel structure at the position of 1 / 2 of the plate thickness is a mixed structure consisting of a bainite phase with an area fraction of 85 to 100% and a ferrite phase with an area fraction of 0 to 15%, and the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less, and the equivalent circle diameter of the largest pore remaining in the center of the steel sheet is 200 μm or less,

[0046] The thickness of the high-strength extra-thick steel plate is 50 mm or more and 100 mm or less.

[0047] The yield strength at 1 / 2 of the plate thickness is 500MPa or more, the Charpy fracture transition temperature at 1 / 2 of the plate thickness is vTrs≤-105℃, and the Kca (-10℃) value is 9000N / mm 3 / 2 above.

[0048] Ceq=C+Mn / 6+Cu / 15+Ni / 15+Cr / 5+Mo / 5+V / 5…(1)

[0049] Here, C, Mn, Cu, Ni, Cr, Mo, and V in formula (1) represent the content (mass %) of each element, and the content of an element not contained is set to 0.

[0050] [2] The high-strength ultra-thick steel plate according to [1], further comprising, in addition to the above-mentioned component composition, one or two selected from the following Group A and Group B in terms of mass %.

[0051] Group A: one or more selected from the group consisting of Ti: 0.030% or less, Nb: 0.050% or less, Cu: 2.00% or less, Ni: 2.50% or less, and Cr: 2.00% or less

[0052] Group B: one or more selected from the group consisting of Mo: 0.50% or less, V: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less

[0053] [3] The high-strength ultra-thick steel plate according to [1] or [2], wherein in the steel structure at the half-thickness position, the segregated grains having a thickness of 100 μm or more have a thickness of 1 mm 2 The number of is less than 2.0.

[0054] [4] The high-strength ultra-thick steel plate according to any one of [1] to [3], wherein the length of the largest pore remaining in the center of the steel plate in the steel structure at the 1 / 2 position of the plate thickness in the plate thickness direction is 100 μm or less.

[0055] [5] A method for producing a high-strength and ultra-thick steel plate, which is the method for producing a high-strength and ultra-thick steel plate according to any one of [1] to [4], wherein:

[0056] The steel material having the above composition is heated to a heating temperature of 1000 to 1200°C.

[0057] Next, hot rolling is carried out under the conditions that the rolling start temperature at the position of 1 / 2 thickness is (Ar3 point + 100) ° C or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite recrystallization temperature range is 25.0% or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite non-recrystallization temperature range is 50.0% or more, and the rolling end temperature at the position of 1 / 2 thickness is Ar3 point or more, and the thickness of the steel billet is 200 mm or more, and the reduction ratio representing the ratio of the thickness of the steel billet to the thickness of the final product is 4.00 or more.

[0058] Next, cooling is carried out under the conditions that the cooling start temperature at the 1 / 2 thickness position is above the Ar3 point, the temperature at the 1 / 2 thickness position is in the temperature range of 700 to 500°C, the average cooling rate is above 3.5°C / s, and the cooling stop temperature at the 1 / 2 thickness position is below 500°C.

[0059] [6] A method for manufacturing a high-strength ultra-thick steel plate according to [5], wherein the hot rolling is further carried out under the conditions that the average reduction rate / pass is 4.5% or more when the temperature at the 1 / 2 position of the plate thickness is within the austenite non-recrystallization temperature range, the rolling end temperature at the 1 / 4 position of the plate thickness is (the rolling end temperature at the 1 / 2 position of the plate thickness - 20)°C or more, and the rolling end temperature at a position 2 mm away from the surface of the steel plate in the plate thickness direction is (the rolling end temperature at the 1 / 2 position of the plate thickness - 30)°C or more.

[0060] [7] The method for producing a high-strength ultra-thick steel plate according to [5] or [6], wherein the hot rolling is further carried out under the condition that the average reduction ratio / pass is 4.0% or more when the temperature at the half thickness position is within the austenite recrystallization temperature range.

[0061] Effects of the Invention

[0062] According to the present invention, the texture of the rolled surface at the half-thickness position is appropriately controlled by a mixed structure formed of bainite and ferrite, and the steel structure at the half-thickness position is refined, so that the toughness and brittle crack propagation characteristics are improved. In addition, according to the manufacturing method of the present invention, since the rolling conditions of the hot rolling process are optimized, the ultra-thick steel plate of the present invention has good internal quality even with a high strength of 500 MPa or more in yield strength, and is also excellent in toughness and brittle crack propagation characteristics.

[0063] For example, by applying the high-strength and ultra-thick steel plate of the present invention to a deck member joined to a hatch side coaming in a strong deck structure of a container ship or a bulk carrier in the shipbuilding field, it helps to improve the safety of the ship. Therefore, the present invention is extremely useful in industry. DETAILED DESCRIPTION

[0064] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.

[0065] First, the reason why the chemical composition of the high-strength ultra-thick steel plate is limited in the present invention is described. In this specification, "%" about the chemical composition means "mass %" unless otherwise specified.

[0066] C: 0.040~0.130%

[0067] C is an element that has the effect of increasing the hardenability of steel and is necessary to achieve the desired strength characteristics. In the present invention, in order to obtain the above-mentioned effect, the C content is set to 0.040% or more. On the other hand, when the C content is greater than 0.130%, not only the weldability is deteriorated, but also a large amount of coarse carbides that become the starting point of fracture are generated, which also has an adverse effect on toughness. Therefore, the C content is in the range of 0.040 to 0.130%. It should be noted that, with respect to the lower limit, the preferred C content is 0.050% or more. With respect to the upper limit, the preferred C content is 0.100% or less.

[0068] Si: 0.020~0.50%

[0069] Si is a necessary component for deoxidation, etc., and is an element that has the effect of increasing the hardenability of steel by inhibiting the formation of coarse carbides. In order to achieve the desired strength characteristics, 0.020% or more of Si is contained. On the other hand, when the Si content is greater than 0.50%, not only the surface properties of the steel are damaged, but also the toughness is extremely deteriorated. Therefore, the Si content is in the range of 0.020 to 0.50%. It should be noted that, with respect to the lower limit, the preferred Si content is greater than 0.050%. With respect to the upper limit, the preferred Si content is less than 0.30%.

[0070] Mn: 1.00~2.50%

[0071] Mn is an element that increases the hardenability of steel and is necessary to achieve the desired strength. In order to obtain the above-mentioned effect, the Mn content is set to 1.00% or more. On the other hand, when the Mn content is high, the strength is excessively increased, so the toughness is reduced, and the alloy cost is excessively increased. From these viewpoints, the Mn content is less than 2.50%. Therefore, the Mn content is in the range of 1.00 to 2.50%. It should be noted that, with respect to the lower limit, the preferred Mn content is more than 1.50%. With respect to the upper limit, the preferred Mn content is less than 2.35%.

[0072] P: 0.020% or less, S: 0.010% or less

[0073] P and S are inevitable impurities in steel. When these contents increase, toughness deteriorates. For extremely thick steel plates with a thickness of 50 mm or more and 100 mm or less, in order to maintain good toughness, the P content is suppressed to 0.020% or less, and the S content is suppressed to 0.010% or less. It should be noted that the P content is preferably 0.015% or less, and more preferably 0.006% or less. The S content is preferably 0.006% or less, and more preferably 0.002% or less.

[0074] It should be noted that there is no particular lower limit on the content of P and the content of S. Excessive reduction of P and S leads to an increase in manufacturing costs, so the content of P and the content of S are each preferably 0.0005% or more, more preferably 0.0010% or more.

[0075] Al: 0.010~0.100%

[0076] Al is an element that acts as a deoxidizer. In order to obtain this effect, the Al content needs to be 0.010% or more. On the other hand, when the Al content is greater than 0.100%, the toughness decreases, and when welding is performed, the toughness of the weld metal portion decreases. Therefore, the Al content is in the range of 0.010 to 0.100%. It should be noted that, with respect to the lower limit, the preferred Al content is 0.020% or more, more preferably 0.040% or more. With respect to the upper limit, the Al content is preferably 0.080% or less, more preferably 0.070% or less, and further preferably 0.050% or less.

[0077] N: 0.0010~0.0100%

[0078] N combines with Al in steel and precipitates in the form of AlN during rolling. It refines the austenite grain size through the pinning effect, thereby improving the strengthening and toughness of the steel. In order to achieve this effect, the N content needs to be 0.0010% or more. On the other hand, when the N content is greater than 0.0100%, the toughness deteriorates. Therefore, the N content is less than 0.0100%. Therefore, the N content is in the range of 0.0010 to 0.0100%. It should be noted that, with respect to the lower limit, the preferred N content is 0.0020% or more, and more preferably 0.0040% or more. With respect to the upper limit, the preferred N content is 0.0070% or less.

[0079] O: 0.0100% or less

[0080] O (oxygen) is an element contained as an inevitable impurity, and its content is specified because it is an element that should be reduced. O forms oxides and becomes the starting point of brittle fracture, thus bringing about adverse effects such as reduced toughness and the subsequent reduction of brittle crack propagation stop characteristics. Therefore, the O content is limited to less than 0.0100%. The O content is preferably less than 0.0050%, more preferably less than 0.0030%. It should be noted that the lower limit of the O content is not particularly limited and can be 0%. Generally, O is an element that is inevitably contained in steel as an impurity, so it can be greater than 0% in industry. In addition, excessive reduction of O will lead to a surge in refining costs, so from the perspective of cost, it is preferred that the O content is more than 0.0020%.

[0081] In the present invention, each element is set within the above range and is contained so that the Ceq (carbon equivalent) (%) defined by the formula (1) satisfies the following range.

[0082] Ceq=C+Mn / 6+Cu / 15+Ni / 15+Cr / 5+Mo / 5+V / 5…(1)

[0083] Here, C, Mn, Cu, Ni, Cr, Mo, and V in formula (1) represent the content (mass %) of each element, and the content of an element not contained is set to 0.

[0084] Ceq: 0.480% or more

[0085] In order to achieve the excellent strength obtained by improving the hardenability of the ultra-thick steel plate of the present invention and the improvement of the brittle crack propagation arrest characteristics accompanied by the development of the texture, the Ceq represented by the formula (1) is adjusted to be above 0.480%. As a result, the hardenability of the steel plate is increased, and even at the 1 / 2 position of the plate thickness where the cooling rate is the smallest, the steel structure becomes bainite on the entire surface, thereby improving the strength. Ceq is preferably above 0.495%. It should be noted that there is no special upper limit for Ceq. When Ceq is excessively increased, the alloy cost becomes too high. Ceq is preferably below 0.560%, and more preferably below 0.545%.

[0086] The above is the basic component composition of the present invention, and the balance is Fe and inevitable impurities.

[0087] By having this basic component composition and satisfying the above-mentioned formula (1), the high-strength ultra-thick steel plate of the present invention can obtain target properties.

[0088] In the present invention, in order to further improve the characteristics, in addition to the basic component composition, one or two groups selected from the group A and group B described below may be contained as needed. It should be noted that each of the following components, Ti, Nb, Cu, Ni, Cr, Mo, V, W, Co, B, Ca, Mg, and REM, may be contained as needed, so these components may be 0%.

[0089] Group A: one or more selected from the group consisting of Ti: 0.030% or less, Nb: 0.050% or less, Cu: 2.00% or less, Ni: 2.50% or less, and Cr: 2.00% or less

[0090] Ti: 0.030% or less

[0091] Ti forms nitrides, carbides or carbonitrides by containing a small amount, which has the effect of refining the grains and improving the toughness of the base material. In order to obtain this effect, it is preferred that the Ti content is 0.005% or more. On the other hand, when the Ti content is greater than 0.030%, the toughness of the base material and the weld heat affected zone decreases. Therefore, when Ti is contained, the Ti content is preferably 0.030% or less, and more preferably 0.025% or less. The Ti content is more preferably 0.010% or more, and further preferably 0.019% or more.

[0092] Nb: 0.050% or less

[0093] Nb has the effect of increasing the hardenability of steel and expanding the non-recrystallization temperature region in rolling (i.e. hot rolling) in the austenite region. In order to obtain this effect, it is preferred that the Nb content is 0.005% or more. On the other hand, when the Nb content is greater than 0.050%, coarse NbC precipitates, which may lead to a decrease in toughness. Therefore, in the case of containing Nb, the Nb content is preferably 0.050% or less, more preferably 0.040% or less. The Nb content is more preferably 0.010% or more, and further preferably 0.020% or more.

[0094] Cu: 2.00% or less

[0095] Cu is an element that improves the hardenability of steel. This element directly contributes to the strength improvement after rolling. At the same time, in order to improve the functions such as toughness, high temperature strength and weather resistance, Cu can be contained. In order to obtain the above-mentioned effect produced by this element, it is preferred that the Cu content is more than 0.01%. On the other hand, when the Cu content is greater than 2.00%, it causes the deterioration of weldability and toughness and the rise of alloy cost. Therefore, when containing Cu, the Cu content is preferably less than 2.00%, more preferably less than 1.00%. The Cu content is more preferably more than 0.05%.

[0096] Ni: 2.50% or less

[0097] Ni is an element that improves the hardenability of steel. Ni directly contributes to the strength improvement after rolling. At the same time, in order to improve the functions such as toughness, high temperature strength or weather resistance, Ni can be contained. In order to obtain the above-mentioned effect produced by this element, it is preferred that the Ni content is more than 0.01%. On the other hand, when the Ni content is greater than 2.50%, it causes the deterioration of weldability and toughness and the increase of alloy cost. Therefore, when containing Ni, the Ni content is preferably less than 2.50%, more preferably less than 2.00%. The Ni content is more preferably more than 0.10%.

[0098] Cr: 2.00% or less

[0099] Cr is an element that improves the hardenability of steel. This element directly contributes to the improvement of strength after rolling. At the same time, Cr may be contained in order to improve functions such as toughness, high temperature strength or weather resistance. In order to obtain the above-mentioned effects produced by this element, it is preferred that the Cr content is 0.01% or more. On the other hand, when the Cr content is greater than 2.00%, it leads to deterioration of weldability and toughness and an increase in alloy cost. Therefore, when Cr is contained, the Cr content is preferably less than 2.00%, more preferably less than 1.00%. More preferably, the Cr content is more than 0.05%.

[0100] Group B: one or more selected from the group consisting of Mo: 0.50% or less, V: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less

[0101] Mo: 0.50% or less

[0102] Mo is an element that improves the hardenability of steel. This element directly contributes to the improvement of strength after rolling. At the same time, in order to improve functions such as toughness, high temperature strength or weather resistance, Mo can be contained. In order to obtain the above-mentioned effect produced by this element, it is preferred that the Mo content is 0.01% or more. On the other hand, when the Mo content is greater than 0.50%, it leads to deterioration of weldability and toughness and an increase in alloy cost. Therefore, when Mo is contained, the Mo content is preferably 0.50% or less, more preferably 0.30% or less. The Mo content is more preferably 0.03% or more.

[0103] V: 0.50% or less

[0104] V is an element that improves the strength of steel by precipitation strengthening in the form of V (CN). This effect is exerted by making the V content 0.001% or more. However, when the V content is greater than 0.50%, there is a situation where toughness decreases. Therefore, when V is contained, the V content is preferably 0.50% or less, more preferably 0.30% or less. The V content is more preferably 0.005% or more.

[0105] W: 0.50% or less

[0106] W is an element that has the effect of increasing the strength of the steel sheet. In order to obtain this effect, the W content is preferably 0.001% or more. On the other hand, when the W content is greater than 0.50%, the weldability is deteriorated and the alloy cost increases. Therefore, when W is contained, the W content is preferably 0.50% or less, and more preferably 0.30% or less. The W content is more preferably 0.005% or more.

[0107] Co: 0.50% or less

[0108] Co is an element that has the effect of increasing the strength of the steel sheet. In order to obtain this effect, the Co content is preferably 0.001% or more. On the other hand, when the Co content is greater than 0.50%, the weldability is deteriorated and the alloy cost increases. Therefore, when Co is contained, the Co content is preferably 0.50% or less, and more preferably 0.30% or less. The Co content is more preferably 0.005% or more.

[0109] B: 0.0100% or less

[0110] B is an element that improves the hardenability of steel in trace amounts. However, when B is contained in an amount greater than 0.0100%, the toughness of the weld is reduced. Therefore, when B is contained, the B content is preferably 0.0100% or less, more preferably 0.0030% or less. In order to increase the strength of the steel plate, the B content is preferably 0.0001% or more, more preferably 0.0005% or more.

[0111] Ca: 0.0100% or less

[0112] Ca refines the structure of the weld heat affected zone and improves toughness. In order to obtain this effect, when Ca is contained, the Ca content is preferably 0.0005% or more, and more preferably 0.0020% or more. On the other hand, when the Ca content exceeds 0.0100%, coarse inclusions are formed, which deteriorates toughness. Therefore, when Ca is contained, the Ca content is preferably 0.0100% or less, and more preferably 0.0050% or less.

[0113] Mg: 0.0100% or less

[0114] Mg, like Ca, refines the structure of the weld heat affected zone and improves toughness. In order to obtain this effect, when Mg is contained, the Mg content is preferably 0.0005% or more, and more preferably 0.0020% or more. On the other hand, when the Mg content exceeds 0.0100%, coarse inclusions are formed, which deteriorates toughness. Therefore, when Mg is contained, the Mg content is preferably 0.0100% or less, and more preferably 0.0050% or less.

[0115] REM: 0.0200% or less

[0116] REM (rare earth metal) refines the structure of the weld heat affected zone like Ca and improves toughness. In order to obtain this effect, when REM is contained, the REM content is preferably 0.0005% or more, and more preferably 0.0015% or more. On the other hand, when the REM content exceeds 0.0200%, coarse inclusions are formed, which deteriorates toughness. Therefore, when REM is contained, the REM content is preferably 0.0200% or less, and more preferably 0.0100% or less.

[0117] <Texture>

[0118] [X-ray intensity ratio of (211) plane in the rolled surface at the position of 1 / 2 plate thickness: 1.70 or more]

[0119] For extremely thick steel plates with a thickness of more than 50 mm and less than 100 mm, in order to improve the brittle crack propagation stopping characteristics, it is necessary to make the X-ray intensity ratio of the (211) plane in the rolled surface at the position of 1 / 2 of the plate thickness be greater than 1.70. When the X-ray intensity ratio of the (211) plane is less than 1.70, the brittle crack tends to progress in a straight line, and as a result, the brittle crack propagation stopping characteristics of the plate thickness are reduced. Therefore, the X-ray intensity ratio of the (211) plane in the rolled surface at the position of 1 / 2 of the plate thickness is greater than 1.70. In order to further improve the brittle crack propagation stopping characteristics, the X-ray intensity ratio of the above-mentioned (211) plane is preferably greater than 1.80, and more preferably greater than 1.90.

[0120] It should be noted that the upper limit of the X-ray intensity ratio of the (211) plane is not particularly specified. From the viewpoint of rolling efficiency and manufacturing load, the X-ray intensity ratio of the (211) plane is preferably 2.50 or less, and more preferably 2.25 or less.

[0121] Here, the X-ray intensity ratio of the (211) plane refers to a numerical value indicating the degree of aggregation of the (211) crystal plane of the target material (high-strength ultra-thick steel plate). As described in the examples described later, the X-ray intensity ratio of the (211) plane is the X-ray diffraction intensity (I (211) ) and the X-ray diffraction intensity of the reflection from the (211) surface of a random standard sample without texture (I 0(211) ) ratio (I (211) / I 0(211) ) to calculate.

[0122] <Steel structure at 1 / 2 plate thickness>

[0123] In the present invention, the steel structure at the position of 1 / 2 of the plate thickness is a mixed structure composed of a bainite phase with an area fraction of 85 to 100% and a ferrite phase with an area fraction of 0 to 15%, and the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less, and the equivalent circle diameter of the largest pore remaining in the center of the steel plate is 200 μm or less.

[0124] [Area fraction of bainite phase: 85-100%]

[0125] In the present invention, the area fraction of the bainite phase at the position of 1 / 2 of the plate thickness needs to be 85% or more. By controlling the steel structure in this way, the (211) plane orientation that is favorable to the brittle crack propagation characteristics can be improved. It should be noted that the area fraction of the above-mentioned bainite phase is more preferably 90% or more. The upper limit of the area fraction of the above-mentioned bainite phase is 100%.

[0126] [Area fraction of ferrite phase at 1 / 2 thickness: 0 to 15%]

[0127] In the high-strength ultra-thick steel plate of the present invention, the area fraction of the ferrite phase at the 1 / 2 position of the plate thickness needs to be 0 to 15%. When the area fraction of the ferrite phase is greater than 15%, the fraction of the hard structure decreases, and the texture of the (211) plane will not be fully developed, so the strength and brittle crack propagation stop characteristics are reduced. Therefore, the area fraction of the ferrite phase at the 1 / 2 position of the plate thickness is set to 15% or less. In order to further improve the strength and brittle crack propagation stop characteristics, the area fraction of the above-mentioned ferrite phase is preferably less than 10%, and more preferably less than 5%.

[0128] In addition, the area fraction in the present invention can be measured by the method described in the examples described later.

[0129] [Average grain size of bainite at the half thickness position: 20 μm or less]

[0130] For the high-strength ultra-thick steel plate of the present invention, in order to improve toughness and improve brittle crack propagation arrest characteristics, it is necessary to make the average grain size of bainite grains in the steel structure at the 1 / 2 position of the plate thickness (average crystal grain size of bainite) 20μm or less. In the case where the above average grain size is greater than 20μm, as the grain size coarsens, the fracture unit of the cleavage fracture of the grain becomes larger, so the toughness and brittle crack propagation arrest characteristics are reduced, and as a result, the brittle crack propagation arrest characteristics of the plate thickness are reduced. The above average grain size is preferably 18μm or less, and more preferably 15μm or less.

[0131] On the other hand, the smaller the average particle size, the more favorable the toughness and brittle crack propagation arrest characteristics are, so there is no particular lower limit. From the perspective of rolling efficiency, 1 μm is the lower limit of the average particle size. Therefore, the average particle size is preferably 1 μm or more, and more preferably 3 μm or more.

[0132] Here, the "grain size" is defined as the equivalent circle diameter of a grain surrounded by a grain boundary (high-angle grain boundary) with an orientation difference of 15° or more from an adjacent grain. In addition, the above-mentioned "average grain size" refers to the average value of the grain size of the grains at the position of 1 / 2 of the plate thickness.

[0133] It should be noted that the average grain size of the crystal grains at the position of 1 / 2 of the plate thickness can be measured by the method described in the examples described later.

[0134] [The equivalent circle diameter of the largest pore remaining in the center of the steel plate: 200 μm or less]

[0135] In the high-strength ultra-thick steel plate of the present invention, the equivalent circular diameter of the largest pore remaining in the center of the steel plate (1 / 2 plate thickness position) needs to be 200μm or less. When the equivalent circular diameter of the largest pore is greater than 200μm, the pore becomes the starting point of fracture and the toughness is significantly reduced. Therefore, the equivalent circular diameter of the largest remaining pore at the 1 / 2 plate thickness position is 200μm or less. In order to further improve the toughness, the above-mentioned equivalent circular diameter is preferably less than 150μm, and more preferably less than 100μm. It should be noted that the lower limit of the above-mentioned equivalent circular diameter is not specifically specified. From the viewpoint of rolling efficiency, the above-mentioned equivalent circular diameter is preferably greater than 25μm, and more preferably greater than 50μm.

[0136] Here, as described above, in order to improve the internal quality, it is effective that the length of the largest pore remaining in the center of the steel plate in the plate thickness direction is 100 μm or less based on the equivalent circle diameter of the largest pore. The reason is as follows.

[0137] In the high-strength ultra-thick steel plate of the present invention, it is preferred that the length of the largest pore remaining in the center of the steel plate in the plate thickness direction is 100 μm or less. When the length of the largest pore in the plate thickness direction is greater than 100 μm, the pore becomes the starting point of fracture, and the toughness may be significantly reduced. In order to further improve the toughness, the length in the plate thickness direction is more preferably 75 μm or less, and more preferably 50 μm or less. It should be noted that the lower limit of the length in the plate thickness direction is not particularly specified. From the viewpoint of rolling efficiency, the length in the plate thickness direction is preferably 10 μm or more, and more preferably 25 μm or more. The length in the plate thickness direction of the largest pore at the 1 / 2 position of the plate thickness can be measured by the method described in the embodiments described later. It should be noted that the "length of the largest pore in the plate thickness direction" is different from the "equivalent circular diameter of the largest pore" mentioned above. The former is an indicator of the defect size of the pore, and the latter is an indicator of the shape of the pore.

[0138] It should be noted that in the present invention, in addition to the above-mentioned steel structure and texture, the following configuration may be further provided.

[0139] [Number density of segregated grains at the position of 1 / 2 plate thickness] (preferred condition)

[0140] Segregated grains with a thickness of 100 μm or more per 1 mm 2 Number of items: 2.0 or less

[0141] Large segregated grains of 100 μm or more deteriorate toughness. Therefore, in the high-strength ultra-thick steel plate of the present invention, the number density of segregated grains of 100 μm or more at a position 1 / 2 of the plate thickness is preferably 2.0 grains / mm. 2It should be noted that, when viewed from the plate thickness direction, the segregated grains are in the shape of an ellipse stretched in the rolling direction, and therefore, in the present invention, the length of the ellipse in the plate thickness direction is referred to as "thickness".

[0142] In addition, when the number density of segregated grains is greater than 2.0 / mm 2 In the case of , the number density of segregated grains that become the starting point of fracture increases, brittle fracture is likely to occur, and toughness may decrease. In order to further improve the strength and brittle crack propagation arrest characteristics, the above number density is preferably 1.5 / mm 2 Below, more preferably 1.0 piece / mm 2 the following.

[0143] The thickness and number density of the segregated grains can be measured by the method described in the examples described later.

[0144] <Strength>

[0145] [Yield strength at 1 / 2 plate thickness: 500 MPa or more]

[0146] The high-strength and ultra-thick steel plate of the present invention has a yield strength of 500 MPa or more measured using a JIS 14A tensile test piece of φ14 mm cut from 1 / 2 of the plate thickness. From the perspective of ensuring the hull strength of large container ships exceeding 24,000 TEU, it is necessary to use a high-strength and thick-walled steel plate. From the perspective of being used in the above-mentioned large container ships, the thickness of the ultra-thick steel plate is 50 mm or more and less than 100 mm.

[0147] <Charpy fracture transition temperature>

[0148] [vTrs at 1 / 2 thickness: -105°C or less]

[0149] For high-strength ultra-thick steel plates with a yield strength of 500 MPa or more, in order to improve the brittle crack propagation stop characteristics, it is necessary to make the vTrs at the 1 / 2 position of the plate thickness below -105°C. When the transformation temperature is higher than vTrs: -105°C (that is, when vTrs is greater than -105°C), cracks tend to propagate in one direction, and as a result, the brittle crack propagation stop characteristics of the plate thickness are reduced. Therefore, in the high-strength ultra-thick steel plate of the present invention, the vTrs at the 1 / 2 position of the plate thickness is below -105°C. In order to further improve the brittle crack propagation stop characteristics, vTrs is preferably below -110°C, and vTrs is more preferably below -120°C.

[0150] In addition, the lower limit of vTrs is not particularly specified. From the viewpoint of rolling efficiency, the above-mentioned vTrs is preferably -160°C or higher, and more preferably -150°C or higher.

[0151] As described in the examples described later, vTrs is evaluated by cutting out a JIS No. 4 impact test piece from a position of 1 / 2 of the plate thickness of a high-strength ultra-thick steel plate and performing a Charpy test.

[0152] <Brittle crack propagation arrest characteristics>

[0153] [Kca(-10℃) value: 9000N / mm 3 / 2 above]

[0154] For high-strength and ultra-thick steel plates with a yield strength of 500 MPa or more, the Kca (-10°C) value needs to be 9000 N / mm to prevent the propagation of brittle cracks in the hull. 3 / 2 In order to further improve the brittle crack propagation arrest characteristics, the Kca value at -10°C is preferably 10000 N / mm 3 / 2 More preferably 11000N / mm 3 / 2 above.

[0155] It should be noted that the lower limit of the Kca value is not particularly specified. From the viewpoint of rolling efficiency, the Kca value at -10°C is preferably 25000 N / mm 3 / 2 Below, more preferably 20000N / mm 3 / 2 the following.

[0156] As described in the examples described later, the Kca value can be evaluated by performing a temperature gradient type standard ESSO test.

[0157] As described above, the high-strength ultra-thick steel plate of the present invention has high strength, high (excellent) brittle crack propagation arrest characteristics, and toughness by adjusting the above-mentioned component composition, texture, and refinement of the steel structure at the 1 / 2 plate thickness position.

[0158] Next, a method for producing a high-strength ultra-thick steel plate according to an embodiment of the present invention will be described.

[0159] The high-strength ultra-thick steel plate of the present invention is produced by subjecting a steel material having the above-mentioned component composition to a heating step, a hot rolling step, and a cooling step under specific conditions described below.

[0160] Each step is described in detail below. Unless otherwise specified, the temperature in each step refers to the temperature at the 1 / 2 position of the steel raw material and the hot-rolled plate thickness. For example, the temperature distribution in the cross section of the steel plate can be calculated by heat transfer analysis and the result can be corrected by the surface temperature of the steel plate.

[0161] <Heating process>

[0162] First, a steel material (steel billet) having the above-mentioned component composition is heated to a heating temperature of 1000 to 1200°C.

[0163] [Heating temperature of steel material: 1000~1200℃]

[0164] When the heating temperature of the steel raw material is lower than 1000°C, the heating temperature is too low, the deformation resistance becomes high, and the load on the hot rolling mill increases, so it is difficult to implement subsequent hot rolling. On the other hand, at a high temperature of more than 1200°C for the heating temperature of the steel raw material, the austenite grains coarsen, and as a result, the toughness decreases, and the desired brittle crack propagation stop characteristics cannot be obtained. In addition, the strength of the steel plate decreases. Moreover, oxidation becomes significant, oxidation loss increases, and the yield rate may decrease. For such reasons, the heating temperature is set to below 1200°C. It should be noted that the above-mentioned heating temperature is preferably above 1050°C, and more preferably above 1080°C. The above-mentioned heating temperature is preferably below 1150°C, and more preferably below 1130°C.

[0165] <Hot rolling process>

[0166] Next, the heated steel raw material is hot rolled under the conditions that the rolling start temperature at the 1 / 2 position of the plate thickness is above (Ar3 point + 100)°C, the cumulative reduction rate when the temperature at the 1 / 2 position of the plate thickness is within the austenite recrystallization temperature range is above 25.0%, the cumulative reduction rate when the temperature at the 1 / 2 position of the plate thickness is within the austenite non-recrystallization temperature range is above 50.0%, and the rolling end temperature at the 1 / 2 position of the plate thickness is above the Ar3 point, and the thickness of the steel billet is above 200 mm, and the reduction ratio representing the ratio of the thickness of the steel billet to the thickness of the final product is above 4.00.

[0167] [Rolling start temperature: (Ar3 point + 100)°C or above]

[0168] When the steel raw material heated in the above-mentioned heating process is hot rolled, if the temperature for starting hot rolling at the position of 1 / 2 of the plate thickness is lower than (Ar3 point + 100) ° C, recrystallization cannot be fully induced in the hot-rolled plate after the hot rolling process. Therefore, the austenite grain size does not become finer and the toughness decreases. As a result, the desired brittle crack propagation stop characteristics cannot be obtained. Therefore, the above-mentioned rolling start temperature is set to be above (Ar3 point + 100) ° C. From the viewpoint of ensuring the time for hot rolling in the non-recrystallization region described later, the above-mentioned rolling start temperature is preferably above (Ar3 point + 150) ° C, and more preferably above (Ar3 point + 200) ° C.

[0169] It should be noted that the upper limit of the rolling start temperature may be determined according to the heating temperature of the steel material. That is, the rolling start temperature is preferably 1150°C or lower, more preferably 1130°C or lower, and further preferably 1000°C or lower.

[0170] It should be noted that the Ar3 point (also referred to as "Ar3 transformation point") (°C) can be calculated according to the following formula (3).

[0171] Ar3 point (℃) = 910-273×C-74×Mn-57×Ni-16×Cr-9×Mo-5×Cu…(3)

[0172] Here, in the formula (3), each element symbol represents the content (mass %) of the element in the steel, and an element not contained is set to 0.

[0173] [Cumulative reduction within the austenite recrystallization temperature range: 25.0% or more]

[0174] Hot rolling is performed with a cumulative reduction rate of 25.0% or more when the temperature at the position of 1 / 2 of the plate thickness is within the austenite recrystallization temperature range. When the cumulative reduction rate in this temperature range is less than 25.0%, the austenite is not sufficiently refined and the toughness is not improved. As a result, the Charpy fracture transformation temperature at the position of 1 / 2 of the plate thickness cannot be reached: below -105°C. In addition, it is not possible to press down within the high temperature range that is effective for the voids inside the press-bonded steel plate, resulting in defects remaining inside the steel plate. The cumulative reduction rate in this temperature range is preferably 40.0% or more, more preferably 50.0% or more, and further preferably 55.0% or more.

[0175] The upper limit of the cumulative reduction rate in this temperature range is not particularly limited. The above-mentioned effect of improving fine graining is saturated, so the cumulative reduction rate in this temperature range is preferably 75.0% or less, more preferably 70.0% or less, further preferably 65.0% or less, and further more preferably 60.0% or less.

[0176] In the case of the component composition of the present invention, the cumulative reduction ratio in the temperature range of 1100 to 950° C. is preferably 25.0% or more.

[0177] [Cumulative reduction ratio within the austenite non-recrystallization temperature range: 50.0% or more]

[0178] Further, hot rolling is performed with a cumulative reduction ratio of 50.0% or more when the temperature at the position of 1 / 2 of the plate thickness is within the austenite non-recrystallization temperature range. By making the cumulative reduction ratio in this temperature range 50.0% or more, the rolling texture developed when rolling the austenite phase changes from austenite to bainite. At this time, by phase transformation along the slip system selected by variant selection, a texture with an X-ray intensity ratio of 1.70 or more in the (211) plane in the rolling surface at the position of 1 / 2 of the plate thickness can be obtained. On the other hand, when the cumulative reduction ratio in this temperature range is less than 50.0%, the grain refinement of bainite becomes insufficient, and the Charpy fracture transformation temperature (vTrs) at the position of 1 / 2 of the plate thickness cannot be reached: -105°C or less. In addition, a texture with an X-ray intensity ratio of 1.70 or more in the (211) plane in the rolling surface at the position of 1 / 2 of the plate thickness cannot be obtained. The cumulative reduction ratio in this temperature range is preferably 55% or more, and more preferably 60% or more.

[0179] The upper limit of the cumulative reduction ratio in this temperature range is not particularly limited. From the viewpoint of not hindering the rolling efficiency, the cumulative reduction ratio in this temperature range is preferably 75% or less, and more preferably 70% or less.

[0180] In the case of the component composition of the present invention, the cumulative reduction ratio in the temperature range of less than 950° C. and 700° C. or more is preferably 50.0% or more.

[0181] [Rolling end temperature at 1 / 2 thickness position: Ar3 point or higher]

[0182] The hot rolling process needs to be completed at a temperature above the Ar3 point (°C) at the rolling end temperature at the position of 1 / 2 of the plate thickness. During hot rolling, when the temperature of the hot-rolled plate is lower than the Ar3 point (°C), the phase transformation to ferrite begins, and the fraction of bainite that increases the X-ray intensity of the (211) plane decreases, so the X-ray intensity ratio of the (211) plane decreases. As a result, excellent brittle crack propagation arrest characteristics cannot be obtained. Moreover, the lower the temperature, the greater the deformation resistance, so there is a problem of increased load on the hot rolling mill. It should be noted that from the viewpoint of making the cooling start temperature of the subsequent process above the Ar3 point (°C), the rolling end temperature is preferably above (Ar3 point + 10)°C.

[0183] The upper limit of the rolling end temperature is not particularly limited. From the viewpoint of rolling efficiency, the rolling end temperature is preferably (Ar3 point + 60)°C or lower, and more preferably (Ar3 point + 50)°C or lower.

[0184] [Pressure reduction ratio: 4.00 or more]

[0185] In the present invention, in addition to the above-mentioned hot rolling conditions, it is also important to control the thickness of the hot-rolled sheet after the hot rolling step.

[0186] Specifically, the rolling in the hot rolling process is controlled so that the thickness of the steel billet is 200 mm or more and the ratio of the thickness of the steel billet to the thickness of the final product (i.e., the reduction ratio) is 4.00 or more. When the reduction ratio is less than 4.00, the grain refinement of the bainite is insufficient, and thus the toughness is not improved. As a result, the Charpy fracture transition temperature at the position of 1 / 2 of the plate thickness cannot be reached: -105°C or less. The thickness of the above-mentioned steel billet is preferably 300 mm or more, and more preferably 350 mm or more. In addition, the above-mentioned reduction ratio is preferably 4.50 or more, and more preferably 5.00 or more.

[0187] The upper limit of the rolling reduction ratio is not particularly limited. From the viewpoint of rolling efficiency, the rolling reduction ratio is preferably 7.50 or less, and more preferably 7.00 or less.

[0188] In the present invention, the effects can be obtained by performing the hot rolling process under the above-mentioned hot rolling conditions. From the viewpoint of more effectively obtaining the effects, it is also effective to further have the following hot rolling conditions in the hot rolling process.

[0189] Specifically, the average reduction ratio / pass when the temperature at the half-thickness position is within the austenite recrystallization temperature range is 4.0% or more.

[0190] In addition, specifically, the average reduction rate / pass when the temperature at the 1 / 2 position of the plate thickness is within the austenite non-recrystallization temperature range is 4.5% or more, and the rolling end temperature at the 1 / 4 position of the plate thickness is (the rolling end temperature at the above-mentioned 1 / 2 position of the plate thickness - 20)°C or more, and the rolling end temperature of the surface layer is (the rolling end temperature at the above-mentioned 1 / 2 position of the plate thickness - 30)°C or more.

[0191] [Average reduction ratio within austenite recrystallization temperature range / pass: 4.0% or more] (optional condition)

[0192] In the hot rolling process, it is preferred to perform hot rolling with an average reduction rate / pass of 4.0% or more when the temperature at the position of 1 / 2 of the plate thickness is within the austenite recrystallization temperature range. When the average reduction rate / pass within this temperature range is less than 4.0%, the fine graining effect produced by the recrystallization of the austenite grains becomes insufficient, and there is a situation where the fine graining of the bainite after the phase transformation is insufficient. In addition, the strain caused by the rolling in the high temperature range that is effective in reducing the voids inside the steel plate cannot be given at the position of 1 / 2 of the plate thickness of the steel plate. As a result, the defects inside the steel plate that become the starting point of the fracture remain in a coarse state, and sometimes the toughness is reduced. The adjustment of the length of the maximum pore in the center of the steel plate in the plate thickness direction can be achieved by controlling the hot rolling conditions. The average reduction rate / pass within this temperature range is more preferably 4.5% or more, further preferably 5.0% or more, and further preferably 6.0% or more.

[0193] It should be noted that the upper limit of the average reduction ratio / pass in this temperature range is not particularly limited. From the viewpoint of manufacturing load, the average reduction ratio / pass in this temperature range is preferably 10.0% or less, more preferably 8.0% or less, and further preferably 7.0% or less.

[0194] [Average reduction ratio within the austenite non-recrystallization temperature range / pass: 4.5% or more] (optional condition)

[0195] In the hot rolling process, it is preferred to carry out hot rolling with an average reduction rate / pass of 4.5% or more when the temperature at the position of 1 / 2 of the plate thickness is within the austenite non-recrystallization temperature range. When the average reduction rate / pass within this temperature range is less than 4.5%, the elongation of the austenite grains becomes insufficient, and there is a situation where the bainite is not finely grained. And in the low temperature range, the reduction under the state where the deformation resistance difference between the plate thickness becomes large becomes insufficient, and the strain amount given to the position of 1 / 2 of the plate thickness decreases. As a result, the segregation of alloy element enrichment that becomes the starting point of fracture cannot be dispersed, and there is a situation where toughness decreases. The average reduction rate / pass within this temperature range is more preferably 5.0% or more, and more preferably 6.0% or more.

[0196] It should be noted that the upper limit of the average reduction ratio / pass in this temperature range is not particularly limited. From the viewpoint of manufacturing load, the average reduction ratio / pass in this temperature range is preferably 10% or less, more preferably 7.0% or less, and further preferably 6.0% or less.

[0197] The above-mentioned “average rolling reduction ratio / pass” refers to the average value of the rolling reduction ratio per pass in rolling within a certain temperature range.

[0198] [Rolling end temperature at 1 / 4 of plate thickness: (rolling end temperature at 1 / 2 of plate thickness - 20)°C or less] (optional condition)

[0199] In the hot rolling process, regarding the rolling end temperature at the 1 / 4 position of the plate thickness, it is preferred to end at a temperature below (rolling end temperature at 1 / 2 of the plate thickness - 20)°C at the 1 / 4 position of the plate thickness. During hot rolling, when the temperature at the 1 / 4 position of the plate thickness of the hot-rolled plate is greater than (rolling end temperature at 1 / 2 of the plate thickness - 20)°C, in the low temperature range, the reduction becomes insufficient under the condition where the difference in deformation resistance between the plate thicknesses becomes large, and the amount of strain applied to the 1 / 2 position of the plate thickness decreases. In addition, the enriched segregation of the alloying elements that serve as the starting point of fracture cannot be dispersed. As a result, toughness decreases. The rolling end temperature is preferably below (Ar3 point - 30)°C.

[0200] It should be noted that the upper limit of the rolling end temperature at the 1 / 4 thickness position is not particularly limited. From the viewpoint of rolling efficiency, the rolling end temperature is preferably (Ar3 point - 50)°C or higher, and more preferably (Ar3 point - 40)°C or higher.

[0201] [Rolling end temperature at a position 2 mm from the steel plate surface in the plate thickness direction: (rolling end temperature at 1 / 2 of the plate thickness - 30)°C or less] (optional condition)

[0202] The hot rolling process is preferably ended at a temperature where the rolling end temperature at a position 2 mm away from the surface of the steel plate in the plate thickness direction is less than (rolling end temperature at 1 / 2 plate thickness - 30) ° C. During hot rolling, when the temperature at a position 2 mm away from the surface of the steel plate of the hot-rolled plate in the plate thickness direction is greater than (rolling end temperature at 1 / 2 plate thickness - 30) ° C, in the low temperature range, the reduction becomes insufficient under the condition where the difference in deformation resistance between the plate thicknesses becomes large, and the amount of strain applied to the 1 / 2 plate thickness position decreases. In addition, the segregation of alloy element enrichment that becomes the starting point of fracture cannot be dispersed. As a result, toughness decreases. The rolling end temperature is preferably below (Ar3 point - 40) ° C.

[0203] It should be noted that there is no particular upper limit on the rolling end temperature at a position 2 mm from the steel plate surface in the plate thickness direction. From the perspective of manufacturing load, the surface rolling end temperature is preferably (Ar3 point - 60) ° C or higher, more preferably (Ar3 point - 50) ° C or higher.

[0204] The above-mentioned "surface layer" refers to a position 2 mm away from the surface of the steel plate in the plate thickness direction.

[0205] <Cooling process>

[0206] Next, the hot rolled plate after hot rolling is cooled under the conditions that the cooling start temperature at the 1 / 2 thickness position is above the Ar3 point, the average cooling rate when the temperature at the 1 / 2 thickness position is in the temperature range of 700 to 500°C is above 3.5°C / s, and the cooling stop temperature at the 1 / 2 thickness position is below 500°C.

[0207] [Cooling start temperature: Ar3 point or above]

[0208] For the hot-rolled plate obtained through the above-mentioned hot rolling process, it is necessary to start cooling at a temperature at which the temperature at the 1 / 2 position of the plate thickness is above the Ar3 point (°C). When the cooling start temperature is lower than the Ar3 point (°C), the strength cannot be improved because a large amount of ferrite is generated in the steel. As a result, the X-ray intensity ratio of the (211) plane decreases, and excellent brittle crack propagation stopping characteristics cannot be obtained. Therefore, the cooling start temperature is set to be above the Ar3 point (°C). The cooling start temperature is preferably above (Ar3 point + 10)°C, and preferably below (Ar3 point + 40)°C.

[0209] [Average cooling rate in the temperature range of 700-500°C: 3.5°C / s or more]

[0210] When the average cooling rate in the temperature range from 700°C to the temperature at the 1 / 2 position of the plate thickness reaching the cooling stop temperature (below 500°C) is less than 3.5°C / s, a large amount of ferrite is generated in the steel due to slow cooling, and therefore the volume fraction of bainite cannot be increased. As a result, the X-ray intensity ratio of the (211) plane decreases, and excellent brittle crack propagation stop characteristics cannot be obtained. In addition, the strength decreases. In the present invention, the average cooling rate in the temperature range of 700 to 500°C at the 1 / 2 position of the plate thickness is 3.5°C / s or more. The average cooling rate in this temperature range is preferably 4.0°C / s or more.

[0211] On the other hand, the upper limit of the average cooling rate in the above temperature range is not particularly limited. In order to avoid an increase in cooling cost due to excessive rapid cooling, the average cooling rate in the above temperature range is preferably 20°C / s or less, more preferably 10°C / s or less.

[0212] The temperature range for measuring the average cooling rate is 700 to 500° C., which causes phase transformation of most austenite structures and greatly contributes to the properties.

[0213] The average cooling rate outside the temperature range of 700 to 500° C. does not have a significant effect on the formation of bainite and is therefore not particularly limited, but is preferably 0.5 to 0.1° C. / s from the viewpoint of production efficiency.

[0214] [Cooling stop temperature: 500°C or less]

[0215] The cooling process needs to be carried out until the temperature at the position of 1 / 2 of the plate thickness reaches 500°C or less. In other words, it needs to be carried out until the cooling stop temperature reaches a temperature below 500°C. When the cooling stop temperature is greater than 500°C, a large amount of ferrite is generated in the steel, so the volume fraction of bainite cannot be increased. As a result, the X-ray intensity ratio of the (211) plane decreases, and excellent brittle crack propagation stop characteristics cannot be obtained. In addition, the strength is reduced. The cooling stop temperature is preferably below 450°C, and more preferably below 400°C. On the other hand, there is no restriction on the lower limit of the cooling stop temperature. When the cooling stop temperature is too low, the shape of the steel plate deteriorates. Therefore, the cooling stop temperature is preferably above 200°C, and more preferably above 300°C.

[0216] Example

[0217] Next, the present invention will be specifically described based on examples. It should be noted that the following examples are preferred examples of the present invention, and the present invention is not limited to these examples.

[0218] The composition of the test steel is shown in Table 1, and the manufacturing conditions are shown in Table 2. Molten steel (steel symbols: A to AD) of each composition shown in Table 1 is melted in a converter and made into steel raw materials by continuous casting. Then, a heating process, a hot rolling process and a cooling process are carried out in sequence under the manufacturing conditions shown in Table 2 to manufacture high-strength ultra-thick steel plates (steel symbols: 1 to 43) with a thickness of 50 to 100 mm. It should be noted that the blank column in Table 1 indicates that the element is not intentionally added, including not only the case where the element is not contained (0%), but also the case where the element is inevitably contained.

[0219]

[0220]

[0221] The obtained high-strength ultra-thick steel plates were evaluated for (1) texture, (2) steel structure, (3) strength, (4) toughness, and (5) brittle crack propagation arrest characteristics by the methods described below.

[0222] (1) Texture

[0223] [X-ray intensity ratio of (211) plane]

[0224] The texture was evaluated by measuring the X-ray intensity ratio of the (211) plane at a position of 1 / 2 of the plate thickness of the steel plate.

[0225] From the obtained high-strength ultra-thick steel plate, a plate-shaped sample with a plate thickness of 1 mm at the half-thickness position, 22 mm in a direction parallel to the rolling direction, and 25 mm in a direction perpendicular to the rolling direction was cut, and the surface parallel to the surface of the sample was mechanically polished and electrolytically polished to prepare a test piece for X-ray diffraction. Using this test piece, an X-ray diffraction measurement was carried out using an X-ray diffraction device using a Mo ray source to obtain the X-ray intensity ratio of the (211) plane. The obtained value is recorded in the "X-ray intensity ratio of the X (211) plane" column of Table 3.

[0226] (2) Steel structure

[0227] [Steel structure at 1 / 2 plate thickness]

[0228] The steel structure at the position of 1 / 2 of the plate thickness was measured as follows.

[0229] The sample is cut from the center of the width of the steel plate and the 1 / 2 position of the plate thickness in such a way that the surface perpendicular to the rolling direction becomes the observation surface. The size of the sample is 20 mm in the plate thickness direction, 10 mm in the direction parallel to the rolling direction, and 1 mm in the direction perpendicular to the rolling direction. The surface perpendicular to the rolling direction of the sample is mirror-polished, and then an optical microscope photograph of the metal structure exposed by corrosion with nitric acid alcohol solution is taken. The shooting part is at the 1 / 2 position of the plate thickness, and the magnification is 200 times. According to the obtained photos, the structure exposed in the form of white blocks is regarded as ferrite, and the remaining part is regarded as bainite. The area fraction is calculated by image analysis, thereby evaluating the area fraction of the bainite phase and the ferrite phase. The obtained values ​​are recorded in the columns of "Bainite phase area fraction" and "Ferrite phase area fraction" in Table 3.

[0230] [Average grain size of bainite at the position of 1 / 2 plate thickness]

[0231] The sample is cut from the center of the width of the steel plate and the 1 / 2 position of the plate thickness in such a way that the surface perpendicular to the rolling direction becomes the observation surface. The size of the sample is 20 mm in the direction of the plate thickness, 10 mm in the direction parallel to the rolling direction, and 1 mm in the direction perpendicular to the rolling direction. The surface perpendicular to the rolling direction of the sample is mirror-polished, and then EBSP analysis is performed on the 1 / 2 position of the plate thickness under the following conditions. The equivalent circle diameter of the structure surrounded by high-angle grain boundaries with an orientation difference of more than 15° with adjacent grains is obtained from the obtained crystal orientation diagram, and the average value of the equivalent circle diameter in the following analysis area is taken as the average effective grain size. The obtained value is recorded in the "Average Grain Size of Bainite" column of Table 3.

[0232] (EBSP condition)

[0233] Accelerating voltage: 20KV, irradiation current: 50nA

[0234] Beam diameter: 50nm

[0235] Analysis area: 1mm×1mm area at the center of the plate thickness

[0236] Step size: 0.4μm

[0237] [Equivalent circular diameter of the largest pore]

[0238] In the detection of defects inside the steel plate, ultrasonic flaw detection is mostly used because it can be inspected non-destructively. However, in this embodiment, in order to accurately confirm the state of the defective part, direct observation is performed to measure the size of the pores. First, 1 to 2 cross sections of the observation sample are cut parallel to the plate width direction at the 1 / 2 position of the plate thickness of the rolled material, and mirror polishing is performed. Next, the prepared sample is observed and photographed using an optical microscope. The magnification is 400 times. The obtained photographs are subjected to image analysis to determine the equivalent circular diameter of each existing pore, and the equivalent circular diameter of the largest pore is calculated. The obtained values ​​are recorded in the "Equivalent Circular Diameter of the Largest Pore" column of Table 3.

[0239] [Length of the largest pore in the thickness direction]

[0240] In the detection of defects inside the steel plate, ultrasonic flaw detection is mostly used because it can be inspected non-destructively. However, in this embodiment, in order to accurately confirm the state of the defective part, direct observation is performed to measure the size of the pores. First, at the 1 / 2 position of the plate thickness of the rolled material, 1 to 2 cross sections are cut from the observation sample parallel to the plate width direction, and mirror polishing is performed. Next, the prepared sample is observed and photographed using an optical microscope. The magnification is 400 times. The obtained photos are image analyzed, the length of each existing pore in the plate thickness direction is measured, and the length of the maximum pore in the plate thickness direction is calculated. Specifically, for each pore, the length in the plate thickness direction is calculated at a spacing of 20μm along the plate width direction, and the maximum value is used as the length in the plate thickness direction. Similarly, the length of the remaining pores in the plate thickness direction is measured, and the maximum value among the obtained values ​​is used as the length of the maximum pore in the plate thickness direction. The obtained values ​​are recorded in the "Length of the Maximum Pore in the Plate Thickness Direction" column of Table 3.

[0241] [The thickness of segregated grains with a thickness of 100 μm or more at the half-thickness position is 1 mm 2 The number of ]

[0242] A plate-shaped sample was cut parallel to the plate width direction of the obtained high-strength ultra-thick steel plate, and EPMA analysis of Mn was performed in a manner including the central segregation portion. Based on the obtained data, the portion where the Mn concentration was 1.25 times or more of the average value of the EPMA measurement range was regarded as the segregation portion, and the thickness and number were measured.

[0243] The thickness of the segregated grains was determined by measuring the length in the plate thickness direction when viewed from the rolling direction as the thickness.

[0244] Then, every 1mm 2 The number of segregated grains in the measurement region was obtained by dividing the segregated grains having a thickness of 100 μm or more in the measurement region by the area of ​​the measurement region. The obtained value is recorded in the column “Number density of segregated grains” in Table 3.

[0245] (EPMA measurement conditions)

[0246] Irradiation current: 100nA

[0247] Beam diameter: 20μm

[0248] ·Measurement area: 3mm in height direction x 20mm in width direction including the central segregation part

[0249] Step length: 20 μm

[0250] (3) Strength

[0251] From the 1 / 2 position of the plate thickness of the obtained ultra-thick steel plate, a JIS 14A test piece of φ14 was cut in a manner such that the direction of the long axis of the test piece was perpendicular to the rolling direction, and a tensile test was performed according to the provisions of JIS Z 2241 (2011) to measure the yield strength (YS) and tensile strength (TS). Here, a yield strength of 500 MPa or more was evaluated as high strength.

[0252] (4) Toughness

[0253] The toughness was evaluated at the Charpy fracture transition temperature at the position of 1 / 2 of the plate thickness.

[0254] From the 1 / 2 position of the plate thickness of the obtained high-strength ultra-thick steel plate, a JIS 4 impact test piece is cut in a manner that the direction of the long axis of the test piece is parallel to the rolling direction, and a Charpy impact test is performed according to the provisions of JIS Z 2242 (2005) to obtain the Charpy fracture transition temperature (vTrs). It should be noted that 3 tests are performed for 1 test temperature, and the brittle fracture rate is calculated from the average value of the 3. Here, vTrs≤-105°C is evaluated as excellent toughness.

[0255] (5) Brittle crack propagation arrest characteristics

[0256] The brittle crack propagation arrest characteristic was evaluated by determining the Kca value.

[0257] In order to evaluate the brittle crack propagation arrest characteristics, a temperature gradient standard ESSO test was performed to obtain the Kca value (Kca(-10℃) at -10℃ (N / mm 3 / 2 )). For the test body, three pieces were cut from each of the obtained high-strength and ultra-thick steel plates. The dimensions of the test body were total thickness × L: 500 × W: 500 (mm). The Kca value was calculated from the results of the three tests. Here, the Kca (-10°C) value was 9000 N / mm 3 / 2 The above test bodies were evaluated to be excellent in brittle crack propagation arrest characteristics.

[0258] Table 3 shows the test results.

[0259]

[0260] The results shown in Table 3 show the following. In the case of the examples of the present invention (manufacturing No. 1 to 16, 35, 38, 42, 43), the component composition and manufacturing conditions are within the scope of the present invention, the texture at the 1 / 2 position of the plate thickness satisfies the X-ray intensity ratio of the (211) plane: 1.70 or more, and the area fraction of the bainite phase satisfies 85% or more, and the average effective grain size of the bainite phase satisfies 20μm or less. As a result, the yield strength at the 1 / 2 position of the plate thickness is 500MPa or more, the Charpy fracture transformation temperature at the 1 / 2 position of the plate thickness is -105°C or less, and the Kca (-10°C) value is 9000N / mm 3 / 2 The above characteristics.

[0261] On the other hand, in the case of comparative examples (manufacturing Nos. 17 to 34, 36 to 37, and 39 to 41), one or more of the component compositions and manufacturing conditions are outside the scope of the present invention, so the texture at the 1 / 2 position of the plate thickness and the steel structure at the 1 / 2 position of the plate thickness cannot be obtained, and the target properties at the 1 / 2 position of the plate thickness are not met.

Claims

1. A high-strength and extremely thick steel plate, It has a composition containing, in mass%, C: 0.040 to 0.130%, Si: 0.020 to 0.50%, Mn: 1.00 to 2.50%, P: 0.020% or less, S: 0.010% or less, Al: 0.010 to 0.100%, N: 0.0010 to 0.0100% and O: 0.0100% or less, and Ceq defined by formula (1) is 0.480% or more, and the balance is Fe and inevitable impurities, The texture has an X-ray intensity ratio of the (211) plane in the rolled surface at a position of 1 / 2 of the plate thickness of 1.70 or more, The steel sheet has a steel structure at a position of 1 / 2 of the plate thickness as described below, wherein the steel structure at the position of 1 / 2 of the plate thickness is a mixed structure consisting of a bainite phase with an area fraction of 85 to 100% and a ferrite phase with an area fraction of 0 to 15%, and the average grain size of bainite grains surrounded by grain boundaries with an orientation difference of 15° or more is 20 μm or less, and the equivalent circle diameter of the largest pore remaining in the center of the steel sheet is 200 μm or less, The thickness of the high-strength extra-thick steel plate is 50 mm or more and 100 mm or less. The yield strength at 1 / 2 of the plate thickness is 500MPa or more, the Charpy fracture transition temperature at 1 / 2 of the plate thickness is vTrs≤-105℃, and the Kca (-10℃) value is 9000N / mm 3 / 2 above, Ceq=C+Mn / 6+Cu / 15+Ni / 15+Cr / 5+Mo / 5+V / 5…(1) Here, C, Mn, Cu, Ni, Cr, Mo, and V in formula (1) represent the content (mass %) of each element, and the content of an element not contained is set to 0.

2. The high-strength extra-thick steel plate according to claim 1, wherein: In addition to the above-mentioned component composition, one or two selected from the following Group A and Group B are contained in terms of mass %, Group A: one or more selected from the group consisting of Ti: 0.030% or less, Nb: 0.050% or less, Cu: 2.00% or less, Ni: 2.50% or less, and Cr: 2.00% or less; Group B: one or more selected from the group consisting of Mo: 0.50% or less, V: 0.50% or less, W: 0.50% or less, Co: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0200% or less.

3. The high-strength extra-thick steel plate according to claim 1, wherein: In the steel structure at the half thickness position, the segregated grains with a thickness of 100 μm or more have a thickness of 1 mm. 2 The number of is less than 2.

0.

4. The high-strength extra-thick steel plate according to claim 2, wherein: In the steel structure at the half thickness position, the segregated grains with a thickness of 100 μm or more have a thickness of 1 mm. 2 The number of is less than 2.

0.

5. The high-strength extra-thick steel plate according to claim 1, wherein: In the steel structure at the position of 1 / 2 of the plate thickness, the length of the largest pore remaining in the center of the steel plate in the plate thickness direction is 100 μm or less.

6. The high-strength and extra-thick steel plate according to claim 2, wherein: In the steel structure at the position of 1 / 2 of the plate thickness, the length of the largest pore remaining in the center of the steel plate in the plate thickness direction is 100 μm or less.

7. The high-strength and extra-thick steel plate according to claim 3, wherein: In the steel structure at the position of 1 / 2 of the plate thickness, the length of the largest pore remaining in the center of the steel plate in the plate thickness direction is 100 μm or less.

8. The high-strength extra-thick steel plate according to claim 4, wherein: In the steel structure at the position of 1 / 2 of the plate thickness, the length of the largest pore remaining in the center of the steel plate in the plate thickness direction is 100 μm or less.

9. A method for producing a high-strength and ultra-thick steel plate, which is the method for producing a high-strength and ultra-thick steel plate according to any one of claims 1 to 8, wherein: The steel material having the above composition is heated to a heating temperature of 1000 to 1200° C. Next, hot rolling is carried out under the conditions that the rolling start temperature at the position of 1 / 2 thickness is (Ar3 point + 100) ° C or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite recrystallization temperature range is 25.0% or more, the cumulative reduction rate when the temperature at the position of 1 / 2 thickness is within the austenite non-recrystallization temperature range is 50.0% or more, and the rolling end temperature at the position of 1 / 2 thickness is Ar3 point or more, and the thickness of the steel billet is 200 mm or more, and the reduction ratio representing the ratio of the thickness of the steel billet to the thickness of the final product is 4.00 or more. Next, cooling is carried out under the conditions that the cooling start temperature at the 1 / 2 thickness position is above the Ar3 point, the temperature at the 1 / 2 thickness position is in the temperature range of 700 to 500°C, the average cooling rate is above 3.5°C / s, and the cooling stop temperature at the 1 / 2 thickness position is below 500°C.

10. The method for producing a high-strength ultra-thick steel plate according to claim 9, wherein: The hot rolling is further carried out under the conditions that the average reduction rate / pass is 4.5% or more when the temperature at the 1 / 2 position of the plate thickness is within the non-recrystallization temperature range of austenite, the rolling end temperature at the 1 / 4 position of the plate thickness is (the rolling end temperature at the 1 / 2 position of the plate thickness - 20)°C or more, and the rolling end temperature at a position 2 mm away from the surface of the steel plate in the plate thickness direction is (the rolling end temperature at the 1 / 2 position of the plate thickness - 30)°C or more.

11. The method for producing a high-strength ultra-thick steel plate according to claim 9, wherein: The hot rolling is further performed under the condition that the average reduction ratio / pass is 4.0% or more when the temperature at the half-thickness position is within the austenite recrystallization temperature range.

12. The method for producing a high-strength ultra-thick steel plate according to claim 10, wherein: The hot rolling is further performed under the condition that the average reduction ratio / pass is 4.0% or more when the temperature at the half-thickness position is within the austenite recrystallization temperature range.

Citation Information

Patent Citations

  • Steel plate having excellent arrest property and its manufacturing method

    JP2002256375A

  • High-strength thick steel plate having excellent brittle crack propagation-stopping performance, and method for producing the same

    JP2008169467A

  • Steel having excellent brittle crack arrest property, and method of producing the same

    JP2011184754A

  • Method for manufacturing thick steel plate

    JP2012172258A

  • Production method for thick steel plate

    WO2011096456A1

Cited By

  • Anti-fatigue extra-thick maritime work steel plate and manufacturing method thereof

    CN120464936A

  • Anti-fatigue super-thick marine steel plate and manufacturing method thereof

    CN120464936B